2001
DOI: 10.1016/s0029-7844(01)01472-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost of pelvic organ prolapse surgery in the United States

Abstract: The annual direct costs of operations for pelvic organ prolapse are substantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
206
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(216 citation statements)
references
References 5 publications
2
206
0
8
Order By: Relevance
“…About 50% of parous women have some degree of pelvic organ prolapse [1] although only 10% are symptomatic [2,3]. Oslen et al [2] reported an 11-12% risk of surgery for prolapse in women reaching 79 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…About 50% of parous women have some degree of pelvic organ prolapse [1] although only 10% are symptomatic [2,3]. Oslen et al [2] reported an 11-12% risk of surgery for prolapse in women reaching 79 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…It conveys a significant burden on individuals and society, even if it rarely threatens the general health and/or life of the patient. In the United States alone, pelvic organ prolapse is thought to lead to over 200,000 surgical procedures per year, with about 30% being re-operations [1,2], resulting in an annual expenditure of over $1 billion [3]. Female pelvic organ prolapse may give rise to symptoms of vaginal fullness and dragging, with the patient eventually noticing a protrusion from the vagina.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for pelvic organ prolapse involves the surgical repair of anatomic defects in pelvic floor fascial support. Each year in the USA, 300,000 to 400,000 women require surgery for pelvic organ prolapse [3] with an annual cost estimated as $1 billion dollars [4].…”
Section: Introductionmentioning
confidence: 99%